A history of Italian citizenship laws during the era of the monarchy (1861-1946) - Bussotti, L. (Advances in Historical Studies, 2016)
This article aims to present the evolution of Italian citizenship from political unification to the end of the Second World War, which in Italy corresponds with the end of the monarchy and the advent of the Republic. In this long period, the central definition of Italian citizenship was given by the Civil Code (1865), the basis of which was Ius sanguinis and the patrilineal system. The 1912 Law on Citizenship changed some aspects of the previous legislation, but did not alter the general legal scenario, despite great pressure from some organised movements such as those formed by Italian expatriates in the Americas. With the advent of fascism (1922), the discourse on the Italian nation became radicalised, but Mussolini’s regime did not pass any organic laws on citizenship. The innovations introduced under fascism were relatively modest; many were directed towards limiting the rights of particular categories of citizens, such as political opponents and Jewish people. Italy reached the beginning of the republican period with a legal apparatus on citizenship that was very similar to the one established for the first time in the Civil Code of 1865. This shows how Italian political classes have given more attention to the orthodoxy of the law than to the need to adapt it to the numerous transformations in Italian society.